Antidepressant activity of 4-amino-5-(alkyl-, aryl-, heteryl)-1,2,4-triazole-3-thione benzylidene derivatives - Ye. S. Pruhlo (Zaporozhye State Medical University, 2018)
Abstract The current market for antidepressants has a number of limitations, they have a high probability of development of adverse reactions, have low latitude and stability of the therapeutic effect, and also have a long latent period of action. Therefore, it seems obvious that there is a need to create new drugs that improve the quality of life, affect the mood and are safe. An analysis of literary sources has shown that derivatives of 1,2,4-triazole have a pronounced antidepressant effect and drugs such as Trazodone and Alprozalam are widely used in medical practice. The purpose of this work was to study antidepressant effects of 1,2,4-triazole derivatives and to make analysis of the dependence between chemical structure and pharmacological activity. Materials and methods. The search of antidepressants in the series of 1,2,4-triazole derivatives was performed on the basis of the classical model of R.D. Porsolt in the modification of E.V. Schetynin. Each animal was immersed for 6 minutes in a vessel filled with water at a temperature of 27 °C. The duration of active swimming was fixed (vigorous movements of all paws with active movement), passive swimming (weak bends of the paws necessary to support the body to swim) and immobilization (no swimming motions). In addition, the number of active swimming periods of different lengths and the number of very short immobilization periods of up to 6 seconds were counted. The index of depression (ID) was calculated due to the ratio of the very short periods number of immobilization to the total number of active swimming periods. The research results are processed by modern statistical methods of analysis using personal computer, including the standard program package Microsoft Office 2013 (Microsoft Excel) and Statistica® for Windows 6.0. The average arithmetic mean (M) and standard mean errors (±m) were calculated. The statistical significance of intergroup differences according to the experimental data was established using Student's t-criterion. To study the dependence of the influence of benzylidene derivatives of 4-amino-5-(alkyl-, aryl-, heteryl)-2,4-dihydro-3H-1,2,4-triazole-3-thione on the duration of passive swimming and the duration of immobilization was carried out by correlation analysis. Results. Benzylidene derivatives of 4-amino-5-(alkyl-, aryl-, heteryl)-1,2,4-triazole-3-thione were used as test substances. The index of depression in the use of fluoxetine decreased to 70.92 % (P < 0.05), and with the use of trazodone to 76.95 % (P < 0.05). Compounds 26 and 32 statistically significantly lowered the index of depression to 86.66 and 81.24 %, respectively, which was higher than the activity of the used comparison drugs. The main indicator of rats despair was the duration of immobilization, decreased to 73.53 % (P < 0.05) and trazodone to 79.55 (P < 0.05) when administered with fluoxetine. When applying 1,2,4-triazole derivatives, the duration of immobilization of compound 32 was reduced to 89.53 % (P < 0.05), and compounds 23 to 87.05 % (P < 0.05). Conclusions. The most active compound according to the results of the study was compound 32, which reduced the average duration of immobilization in the experimental group to 89.53 % and had a rather low index of depression (0.34 ± 0.08, P < 0.05).